Ultra-micro sized, high performance neodymium iron boron sintered magnet and its manufacturing method
Patent Information
- Application Number
- JP2023209981
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-12-13
- Filing Date
- 2023-12-13
- Publication Date
- 2025-03-31
- Estimated Expiration
- 2043-12-13
AI Technical Summary
【0054】 〔発明の効果〕 本発明は、ネオジム鉄ボロン系焼結磁石及びその製造方法を提供し、ネオジム鉄ボロン系粉末の製粉プロセスにM’Si合金粉末及び/又はM’SiFe合金粉末を添加することにより、微小キャビティ内の粉末落下メカニズムを最適化し、ビレットの焼結前の初期充填密度の均一性を向上させ、多段階段及び振動圧力を結合して緻密に均一化する焼結プロセスにより、均一にニアネットシェイプに造形するネオジム鉄ボロン系永久磁石を形成する。
Smart Images

Figure 0007654058000002 
Figure 0007654058000003 
Figure 0007654058000004
Abstract
Description
Detailed Description of the Invention
[0001] This application claims priority to a prior application, bearing patent application number 202211601298.2 and entitled "Ultra-micro-sized high-performance neodymium-iron-boron sintered magnet and manufacturing method thereof," filed with the State Intellectual Property Office of the People's Republic of China on December 13, 2022. The above prior application is incorporated herein by reference in its entirety.
[0002] [Technical field] The present invention belongs to the field of rare earth permanent magnet materials, and more specifically, to ultra-microsized, high-performance neodymium-iron-boron sintered magnets and a method for producing the same.
[0003] [Background technology] With the development of science and technology, the application of NdFeB sintered magnets in the smart electric industry is increasing more and more, but the products in this industry are small and high precision, so the traditional NdFeB powder can no longer meet the fluidity and filling uniformity in the small mold cavity. In order to obtain NdFeB materials with ideal dimensions, shapes and uniform structures, they are usually obtained by pressing multiple sizes of mold cavities (the size of the mold cavity is relatively large) to reduce the influence of powder fluidity. After sintering, a certain amount of mechanical cutting is performed to manufacture the final product, which wastes a lot of resources, increases the production cost and extends the production cycle, so that the improvement of powder fluidity and uniformity in the micro-cavity is a challenge.
[0004] At present, it has been reported that the problem of poor powder material inclusion and uniformity in the compact is solved by adding oxide, fluoride or fluoride oxide to the powder compact of NdFeB magnet, but after the oxide, fluoride or fluoride oxide is introduced into the powder material, oxygen or fluorine is further increased at the crystal grain boundaries of the NdFeB magnet, which tends to deteriorate the performance of the finished magnet. Therefore, how to solve the flowability and filling uniformity problems of fine-sized NdFeB product powder at low cost and improve the uniformity of the dimensions and performance of the magnet after sintering has become a technical problem that needs to be solved as soon as possible.
[0005] Summary of the Invention The present invention provides a neodymium-iron-boron based sintered magnet comprising the following elements: R: its mass content is 26% to 30%, Fe: its mass content is 60% or more; B: its mass content is 0% to 1.5%, M: its mass content is 0% to 3%, Si: its mass content is 0.05% to 0.2%.
[0006] According to an embodiment of the present invention, R comprises at least Pr and / or Nd, and optionally comprises or does not comprise one or more of Dy, Tb, Ho, Gd, Ce, La, Y.
[0007] According to an embodiment of the present invention, M is one or more selected from Ti, Zr, V, Nb, Cu, Zr, Al and Ga elements, and M does not include Co.
[0008] According to an embodiment of the present invention, the neodymium-iron-boron based sintered magnet does not contain Co.
[0009] According to an embodiment of the present invention, in the neodymium-iron-boron based sintered magnet, the mass content of R is, for example, 27%, 28%, or 29%.
[0010] According to an embodiment of the present invention, in the neodymium-iron-boron based sintered magnet, the mass content of Fe is, for example, 60%, 65%, 70%, 75%, or 80%.
[0011] According to an embodiment of the present invention, in the neodymium-iron-boron based sintered magnet, the mass content of B is, for example, 0.5%, 1%, or 1.5%.
[0012] According to an embodiment of the present invention, in the neodymium-iron-boron based sintered magnet, the mass content of M is, for example, 0.5%, 1%, 1.5%, 2%, or 2.5%.
[0013] According to an embodiment of the present invention, in the neodymium-iron-boron based sintered magnet, the mass content of Si is, for example, 0.1% or 0.15%.
[0014] According to an embodiment of the present invention, the Nd-Fe-B based sintered magnet includes a main phase and a grain boundary phase, the grain boundary phase further includes an R-rich phase, and the mass content of R in the R-rich phase is ≧30%, for example, 40%, 50%, or 70%.
[0015] According to an embodiment of the present invention, in the neodymium-iron-boron based sintered magnet, Si is enriched in the R-rich phase, and the mass content of Si therein is 1% to 5%, for example 2%, 3%, or 4%.
[0016] According to an embodiment of the present invention, the size of the neodymium iron boron based sintered magnet is a length of 10 mm to 20 mm, a press height of 8 mm to 15 mm, and an orientation length of 10 mm to 29 mm, for example, a length of 15 mm ± 0.5 mm, a press height of 10 mm ± 0.5 mm, and an orientation length of 15 mm ± 0.5 mm.
[0017] According to an embodiment of the present invention, the dimensional uniformity of the odymium-iron-boron based sintered magnet is excellent. Preferably, the dimensional polar difference of the neodymium-iron-boron based sintered magnet is Δmax≦0.5 mm.
[0018] According to an embodiment of the present invention, the weight of the neodymium-iron-boron based sintered magnet is less than 50 g.
[0019] According to an embodiment of the present invention, the neodymium-iron-boron based sintered magnet has at least one of the following magnetic properties: Br is selected from 13.8 kGs to 14.8 kGs, for example 14.5 kGs, 14.6 kGs, 14.7 kGs; Hcj is selected from 14 kOe to 16 kOe, for example 15 kOe.
[0020] The present invention further provides a method for producing the above-mentioned neodymium-iron-boron based sintered magnet, specifically comprising the steps of: (1) producing RFeBM scales; (2) preparing an additive; (3) milling the RFeBM scales and mixing them with the additives to obtain a mixed powder; (4) forming the mixed powder into a green compact, and then carrying out a sintering process to obtain the neodymium-iron-boron sintered magnet.
[0021] According to an embodiment of the present invention, in step (1), the RFeBM flakes are composed of the following elements, in parts by weight: R: its mass content is 26% to 30%, Fe: its mass content is 60% or more; B: its mass content is 0% to 1.5%, M: Its mass content is 0% to 3%.
[0022] According to an embodiment of the present invention, R comprises at least Pr or Nd, and optionally comprises or does not comprise one or more of Dy, Tb, Ho, Gd, Ce, La, Y.
[0023] According to an embodiment of the present invention, M is one or more selected from Ti, Zr, V, Nb, Cu, Zr, Al and Ga elements, and M does not include Co.
[0024] According to an embodiment of the present invention, in step (2), the additive comprises M'Si alloy powder and / or M'SiFe alloy powder, where M' is one or more selected from Al, Mg, Cu, Ni, Nb, Zr, and Ti metal elements.
[0025] According to an embodiment of the present invention, the powder particle size of the additive is 8-30 μm, preferably 10-15 μm.
[0026] According to an embodiment of the present invention, the M'Si alloy powder contains 30wt% to 70wt% M' (eg, 40wt%, 50wt%, 60wt%) and 15wt% to 35wt% Si (eg, 20wt%, 25wt%, 30wt%).
[0027] According to an embodiment of the present invention, the M'SiFe alloy powder contains 20wt% to 30wt% M' (eg, 25wt%), 10wt% to 15wt% Si (eg, 11wt%, 12wt%, 13wt%, 14wt%), and the remainder is Fe.
[0028] According to an embodiment of the present invention, the additive includes M'Si alloy powder and / or M'SiFe alloy powder. Preferably, the additive includes M'Si alloy powder and M'SiFe powder, and the mass ratio thereof is (1-4):1, for example, 1:1, 2:1, 3:1, 4:1.
[0029] The present invention selects M'Si alloy and / or M'SiFe alloy powder as the additive, which has wear resistance and is not easily crushed to form ultrafine powder when added in HD or jet mill process; the particle size of the additive is slightly larger than that of the RFeBM powder, so that the RFeBM powder can be more effectively dispersed in the mixing process after jet milling, which increases the overall powder fluidity in the pressing process and improves the dimensional uniformity of the product; on the other hand, in the sintering process, when the content of the neodymium-rich phase in the RFeBM powder is higher than that of the additive alloy powder, the additive will be dispersed and fused or coated on the additive alloy powder, so that the additive will be uniformly dispersed at the grain boundary phase; the additive used in the present invention contains Si element, which can improve the thermal stability of the neodymium-iron-boron magnet, and improve Hcj, so that a neodymium-iron-boron magnet with uniform dimensions and components and high stability is finally obtained.
[0030] The present inventors have found that in the sintering process, some of the Si elements in the additives dissolve in the thin phase positions at the edges of the main phase, occupy the crystal sites of Fe, form new grain boundary phases, or dissolve in the eutectic phase, affect the eutectic temperature, change the wettability and surface tension of the main phase, and further improve the distribution characteristics of the neodymium-rich phase at the grain boundaries. The Si elements also have the effect of improving the high temperature coefficient and reducing the magnetic induction temperature coefficient α. Other parts of the Si elements form new precipitation phases in the neodymium-rich phase, and are dispersed and fused or coated in the neodymium-rich phase, and are uniformly distributed in the neodymium-rich phase, improving the distribution morphology of the neodymium-rich phase at the grain boundaries. The mass fraction of Si in the neodymium-rich phase is 1% to 5%.
[0031] According to an embodiment of the present invention, in step (3), the milling refers to producing RFeBM powder from RFeBM flakes by methods known in the art. Preferably, the particle size of the RFeBM powder is smaller than the powder particle size of the additive.
[0032] According to an embodiment of the present invention, in step (3), the milling includes hydrogen pulverization milling and jet milling.
[0033] According to an embodiment of the present invention, in step (3), the mixing refers to adding the additive during the milling process (e.g., adding during the hydrogrinding milling and / or jet milling process) or adding the additive after milling is completed.
[0034] According to an embodiment of the present invention, in step (3), the mass ratio of the RFeBM powder to the additive is 1000:(0-5), preferably 1000:3.
[0035] The additive of the present invention is selected from M'Si alloy and / or M'SiFe alloy powder, and the RFeBM powder is mixed with the additive and then gradually crushed by friction and collision to improve the particle size and frequency distribution of the RFeBM powder, thereby obtaining RFeBM powder with an ideal particle size and uniformity. Since the additive has high wear resistance, the particle size of the additive remains constant during mixing, but during the pressing process, the powder particle size of the additive is larger than the particle size of the RFeBM powder, so the roughness of the mixed powder is increased to improve the fluidity of the RFeBM powder, and the powder can be uniformly filled into the cavity.
[0036] According to an embodiment of the present invention, in step (4), the density of the green compact is 4 to 5 g / cm 3 , e.g., 4.1 g / cm 3 , 4.2g / cm 3 , 4.3g / cm 3 , 4.4g / cm 3 , 4.5g / cm 3 , 4.6g / cm 3 , 4.7g / cm 3 , 4.8g / cm 3 , 4.9g / cm 3 , 5g / cm 3 It is.
[0037] According to an embodiment of the present invention, in step (4), the size of the green compact is a length of 12 mm to 24 mm, a press height of 9.2 mm to 17.2 mm, and an orientation length of 14 mm to 38.5 mm.
[0038] According to an embodiment of the present invention, in step (4), the compacting can be carried out using methods known in the art, provided that the compact is obtained.
[0039] Preferably, the method for producing the green compact includes pressing under a magnetic field condition. Further, the magnetic field condition may be selected from conditions known in the art, for example, ≧1.8 T.
[0040] Preferably, after press molding, an isostatic pressure treatment may be performed. The isostatic pressure treatment may be performed under conditions selected from those known in the art.
[0041] According to an embodiment of the present invention, in step (4), the sintering process includes stepwise heating, vibration pressure sintering, and cooling. The present invention uses the heating and cooling method to prevent burning in the primary sintering and avoid the generation of large crystal grains, while the vibration pressure of the cavity promotes the flow of the Nd-rich phase coating powder alloy, making the structure more uniform and stabilizing the performance.
[0042] According to an embodiment of the present invention, the stepwise temperature increase conditions are a heat treatment temperature of 100 to 1200° C., preferably 100 to 1100° C., and a heat treatment warming time of 0.5 h to 20 h, preferably 1 to 12 h.
[0043] Preferably, the stepwise temperature increase includes a multi-stage heating treatment, preferably 3 to 6 stages, in which the heating temperature in each stage may be the same or different, and the heating time may be the same or different.
[0044] Preferably, the heating step may be performed under inert gas conditions or under vacuum, for example, some heating steps are performed under inert gas conditions, and the inert gas is selected from gases known in the art, for example, Ar.
[0045] Preferably, the stepwise temperature increase includes a first step of increasing the temperature to 100-450° C. and maintaining the temperature for 0.5-2 hours, a second step of increasing the temperature to 400-650° C. and maintaining the temperature for 0.5-2 hours, a third step of increasing the temperature to 600-900° C. and maintaining the temperature for 0.5-2 hours, and a fourth step of increasing the temperature to 1000-1100° C. and maintaining the temperature for 1-3 hours. Exemplarily, the stepwise temperature increase includes a first step of increasing the temperature to 350° C. and maintaining the temperature for 0.5-2 hours, a second step of increasing the temperature to 600° C. and maintaining the temperature for 0.5-2 hours, a third step of increasing the temperature to 860° C. and maintaining the temperature for 0.5-2 hours, and a fourth step of increasing the temperature to 1030° C. and maintaining the temperature for 1-3 hours.
[0046] According to an embodiment of the present invention, the vibration pressure sintering includes at least one gas-filled temperature decrease (preferably 2 to 3 times) and at least one vacuum-filled temperature increase (preferably 2 to 3 times), in which the gas-filled temperature decrease and the vacuum-filled temperature increase are performed alternately.
[0047] Preferably, the gas-filled temperature reduction refers to filling with an inert gas and lowering the temperature to 900 to 1050° C., and the inert gas has the meaning as described above. Furthermore, the pressure at which the inert gas is filled is 0 to 50 kPa, preferably 0 to 30 kPa, for example, 10 kPa, 15 kPa, 20 kPa, or 25 kPa.
[0048] Preferably, the above-mentioned vacuum evacuation and heating refers to evacuation and heating up to 1000 to 1100°C.
[0049] Preferably, the vibration pressure sintering includes filling with an inert gas at 0 to 30 kPa, decreasing the temperature to 900 to 1050°C, keeping the temperature for 0.5 to 1 hour, drawing a vacuum, increasing the temperature to 1000 to 1100°C, keeping the temperature for 1 to 3 hours, filling with an inert gas at 0 to 30 kPa, decreasing the temperature to 900 to 1050°C, keeping the temperature for 0.5 to 1 hour, drawing a vacuum, increasing the temperature to 1000 to 1100°C, and keeping the temperature for 1 to 3 hours.
[0050] For example, the vibration pressure sintering includes filling with Ar 0-30 kPa, decreasing the temperature to 980°C, keeping the temperature for 0.5-1 hour, evacuating, increasing the temperature to 1050°C, keeping the temperature for 1-3 hours, filling with Ar 0-30 kPa, decreasing the temperature to 1000°C, keeping the temperature for 0.5-1 hour, evacuating, and further increasing the temperature to 1070°C, keeping the temperature for 1-3 hours.
[0051] According to an embodiment of the present invention, the cooling and decreasing temperature refers to cooling to 100°C or less after the vibration pressure sintering. In the present invention, the cooling and decreasing temperature can be performed by selecting a method known in the art, for example, first cooling naturally, and then filling with an inert gas of 70 to 90 KPa to cool to 100°C or less.
[0052] According to an embodiment of the present invention, in the stepwise heating, vibration pressure sintering and cooling / lowering, the heating rate during heating is 5-10° C. / min, and the cooling rate during cooling is 3-8° C. / min.
[0053] The present invention further provides a neodymium-iron-boron based sintered magnet produced by the above production method.
[0054] [Effects of the Invention] The present invention provides a NdFeB-based sintered magnet and a manufacturing method thereof, in which the powder dropping mechanism in the microcavity is optimized by adding M'Si alloy powder and / or M'SiFe alloy powder to the milling process of NdFeB-based powder, thereby improving the uniformity of the initial filling density before sintering the billet, and forming a NdFeB-based permanent magnet that is uniformly shaped to a near-net shape through a dense and uniform sintering process that combines multi-stage stages and vibration pressure.
[0055] The present invention selects M'Si alloy and / or M'SiFe alloy powder as the additive, which has wear resistance and is not easily crushed to form ultrafine powder when added in HD or jet mill process, and the particle size of the additive is slightly larger than that of RFeBM powder, so that the RFeBM powder can be more effectively dispersed in the mixing process after jet milling, which increases the overall powder fluidity in the pressing process and improves the dimensional uniformity of the product. Meanwhile, in the sintering process, when the content of neodymium-rich phase in the RFeBM powder is higher than that of the powder alloy of the additive, the additive can be dispersed and fused or coated with the alloy powder, and further multi-stage temperature increase / decrease and vibration pressure processes are carried out, so that the additive can be uniformly dispersed at the position of the grain boundary phase. Since the additive used in the present invention contains Si element, the thermal stability of the NdFeB magnet can be improved, and the Hcj can be improved, so that a NdFeB magnet with uniform dimensions and components and high stability performance can be finally obtained.
[0056] BRIEF DESCRIPTION OF THE DRAWINGS FIG. 1 is a schematic diagram of a neodymium-iron-boron sintered magnet produced according to the present invention.
[0057] FIG. 2 is an EPMA detection image of Si element in the sample of Example 1.
[0058] FIG. 3 is an EPMA detection image of Si element in the sample of Comparative Example 2.
[0059] [Mode for carrying out the invention] The technical solution of the present invention will be described in more detail below with reference to specific examples. It should be understood that the following examples are merely illustrative and interpretive of the present invention and should not be interpreted as limiting the scope of the claims of the present invention. Any technology realized based on the above content of the present invention is included in the scope of the claims of the present invention.
[0060] Unless otherwise specified, all materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0061] Example 1 The method for producing a neodymium-iron-boron based sintered magnet is as follows.
[0062] (1) RFeBM flakes were manufactured by melting method. Each raw material was melted in an argon gas atmosphere, and the composition of the raw materials was as follows (mass fraction): 30% PrNd, 1.0% B, 0.16% Ti, 0.2% Cu, 0.2% Ga, and the remainder was Fe. Each raw material was prepared in the above raw material composition ratio and placed in a melting furnace. After the alloy was melted, it was heated to 1450°C and kept at that temperature for 5 minutes, then cooled to 1400°C and cast, and a quick-setting sheet with an average thickness of 0.25 mm was obtained by melt spinning.
[0063] (2) M'Si alloy powder was prepared.
[0064] The Al-Si alloy powder with a Si content of 20% had a particle size of 10 μm±2 μm.
[0065] (3) Milling: The RFeBM flakes from step (1) were crushed into HD powder by hydrogen crushing process, and the Al-Si alloy powder from step (2) was added in a ratio of 0.3% of the weight of the HD powder. After mixing for 3 hours, the mixture was jet-milled to obtain a mixed powder, in which the particle size of the RFeBM gas jet milled powder was controlled to be (2.8±0.2) μm. Then, the press processing formulation was added to the mixed powder and stirred for 3 hours, and then the mixture was transferred to the press processing process.
[0066] (4) Press processing: The mixed powder obtained in step (3) after the addition of the molding preparation was pressed into a powder compact under a magnetic field (specifically, 2 T), and then subjected to isostatic pressing to form a powder compact of approximately 4.6 g / cm3.
[0067] (5) Sintering: The multi-stage and vibration pressure sintering process is as follows: in the first stage, the temperature is raised to 350°C and kept at 40min; in the second stage, the temperature is raised to 600°C and kept at 1h; in the third stage, the temperature is raised to 860°C and kept at 2h; in the fourth stage, the temperature is raised to 1030°C and kept at 3h; in the fifth stage, Ar gas is filled at 10kPa, the temperature is lowered to 980°C and kept at 0.5h; in the sixth stage, the vacuum is drawn to 10Pa or less, the temperature is raised to 1050°C and kept at 2h; in the seventh stage, Ar gas is filled at 10kPa, the temperature is lowered to 1000°C and kept at 0.5h; in the eighth stage, the vacuum is drawn to 10Pa or less, the temperature is raised again to 1070°C and kept at 3h; after the end of the keeping, the furnace is first cooled in an empty furnace, and then refilled with inert gas at 70-90KPa and cooled to below 100°C. After that, the vacuum was drawn to below 10 Pa, the temperature was raised to 520°C, and the aging temperature was maintained for 6 hours. After that, an inert gas of 70 to 90 KPa was filled and ventilated to cool to room temperature, and then the magnet was removed to obtain a neodymium-iron-boron sintered magnet 1.
[0068] The neodymium-iron-boron sintered magnets produced in this example were small magnets with dimensions of 15 mm (length) x 15 mm (orientation length) x 10 mm (press height), unit weight of approximately 17.1 g, and a dimensional tolerance of ±0.5 mm.
[0069] The Si content in the neodymium-iron-boron based sintered magnet components produced in this example was 0.06%.
[0070] Example 2 The manufacturing method of the neodymium iron boron based sintered magnet of Example 2 was basically the same as that of Example 1, except that in step (2), the Si content in the Al-Si alloy powder was 25% and the particle size was 10 μm±2 μm, and the rest was the same as that of Example 1, and a neodymium iron boron based sintered magnet 2 was obtained.
[0071] Example 3 The manufacturing method of Example 3 was basically the same as that of Example 1, except that in step (2), the Si content in the Al-Si alloy powder was 30% and the particle size was 10 μm±2 μm, and the rest was the same as that of Example 1, and a neodymium iron boron based sintered magnet 3 was obtained.
[0072] Example 4 The manufacturing method of the neodymium iron boron based sintered magnet of Example 4 was basically the same as that of Example 1, except that in step (3), the RFeBM flakes were crushed by a hydrogen crushing process and jet milled to obtain RFeBM powder (particle size 2.8±0.2 μm), and then Al-Si alloy powder was added in a ratio of 0.3% of the RFeBM powder weight, and the two powders were mixed together for 3 hours to obtain a mixed powder. The rest was the same as that of Example 1, and a neodymium iron boron based sintered magnet 4 was obtained.
[0073] Example 5 The manufacturing method of the neodymium iron boron sintered magnet of Example 5 is basically the same as that of Example 1, except that in step (5), the sintering process does not adopt temperature rise and fall and vibration pressure sintering, and the specific sintering process is to raise the temperature to 350°C in the first stage and keep it at that temperature for 40 min, raise the temperature to 600°C in the second stage and keep it at that temperature for 1 h, raise the temperature to 860°C in the third stage and keep it at that temperature for 2 h, raise the temperature to 1030°C in the fourth stage and keep it at that temperature for 3 h, and continue to raise the temperature again to 1070°C in the fifth stage and keep it at that temperature for 3 h, and after the end of the keeping, first cool in an empty furnace, refill with inert gas at 70 to 90 KPa, and cool to below 100°C. After that, the magnet is evacuated to below 10 Pa, and then reheated to 520°C, and aged for 6 h, and then filled with inert gas at 70 to 90 KPa, blown, cooled to room temperature, and pulled out to obtain the neodymium iron boron sintered magnet 5.
[0074] Comparative Example 1-1 The manufacturing method of the neodymium iron boron based sintered magnet of Comparative Example 1-1 was basically the same as that of Example 1, except that in step (3), no Al-Si alloy powder was added, and the rest was the same as that of Example 1, thereby obtaining a neodymium iron boron based sintered magnet D1-1.
[0075] Comparative Example 1-2 The manufacturing method of the neodymium iron boron based sintered magnet of Comparative Example 1-2 was basically the same as that of Example 1, except that in step (2), the Si content in the Al-Si alloy powder was 40%, and the rest was the same as that of Example 1. A neodymium iron boron based sintered magnet was obtained and designated D1-2.
[0076] Comparative Example 2 The method for producing the neodymium-iron-boron based sintered magnet of Comparative Example 2 was basically the same as that of Example 1, with the following differences.
[0077] (1) RFeBM flakes were produced by melting. Each raw material was melted in an argon gas atmosphere, and the composition of the raw materials was as follows: 30% PrNd, 1.0% B, 0.16% Ti, 0.2% Cu, 0.2% Ga, the remainder being Fe, and an Al-Si alloy powder with a Si content of 20% and a particle size of 10 μm ± 2 μm was added at a ratio of 0.3% of the weight of the raw material. The above raw materials and alloy powder were placed in a melting furnace, the alloy was melted, and then the temperature was raised to 1450 ° C and kept at that temperature for 5 min, and then cooled to 1400 ° C and cast, and a quick-setting sheet with an average thickness of 0.25 mm was obtained by the melt spinning method.
[0078] (2) Milling: The RFeBM flakes from step (1) above were crushed into HD powder by a hydrogen crushing process, then mixed for 3 h, and then jet milled to obtain mixed powder, in which the particle size of the RFeBM gas jet milled powder was controlled to (2.8±0.2) μm. The pressed formulation was then added to the mixed powder and stirred for 3 h before being transferred to the pressing process.
[0079] The pressing and sintering steps were the same as in Example 1, and ultimately a neodymium-iron-boron sintered magnet D-2 was obtained.
[0080] Comparative Example 3 The manufacturing method of the neodymium iron boron based sintered magnet of Comparative Example 3 was basically the same as that of Example 1, except that in step (2), the Si content in the Al-Si alloy powder was 20% and the particle size was 4 μm±2 μm, and the rest was the same as that of Example 1, and a neodymium iron boron based sintered magnet D-3 was obtained.
[0081] The measurement results for the above examples and comparative examples are shown in Table 1.
[0082] [Table 1] In Table 1, the measurement process of Δmax (extreme difference) is as follows:
[0083] Ten magnets were taken from each of the examples and comparative examples above, and each was divided into nine inspection groups. A vernier caliper was used to perform oblique three-point measurements of each magnet in the length direction, orientation length direction, and press height direction. The maximum value max and minimum value min of the three directions corresponding to the magnet in each inspection group were recorded. The differences between the maximum value max and minimum value min of the three directions corresponding to each group were then taken, and the polar difference Δ1max in the length direction, Δ2max in the orientation length direction, and Δ3max in the press height direction of each group were obtained, and the polar difference Δmax for each group was calculated as Δ1max+Δ2max+Δ3max) / 3.
[0084] The magnetic properties in Table 1 were measured using a magnetic tester.
[0085] According to the measurement results in Table 1, Comparing Examples 1, 2 and 3, it can be seen that in the added M'Si alloy powder, so long as the M:Si mass ratio is within the range of (2~5:1), the dimensional polar difference Δmax and magnetic properties do not fluctuate significantly, and as the Si content in the magnet increases, the Br of the magnet decreases moderately and the Hcj increases moderately, but the fluctuations are relatively small.
[0086] Comparing Example 1 and Example 4, it can be seen that adding additives before or after jet milling does not significantly affect the size and performance of the magnets.
[0087] Comparing Example 1 and Example 5, it can be seen that without the use of a dense and uniform sintering process with multiple stages and oscillating pressure, the dimensional uniformity and magnetic performance of the magnets were both affected to a certain extent, for example, the magnet dimensions fluctuated greatly, the pole difference increased, and the denseness of the magnets decreased, and as a result, the Br and Hcj of the magnets were both steadily reduced.
[0088] Comparing Example 1 and Comparative Example 3, it can be seen that when the particle size of the alloy powder corresponds to that of the RFeBM powder, the dimensional uniformity and magnetic properties of the magnet are both affected to different degrees; among them, since the particle sizes of the two powders correspond to each other, the effect of dispersing to improve distribution cannot be achieved, and the fluidity of the mixed powder is not obviously improved, so the dimensions of the magnet fluctuate somewhat greatly, the polar difference is somewhat high, and the corresponding magnet density is poor, resulting in the Br and Hcj of the magnet decreasing to different degrees.
[0089] Comparing Example 1 and Comparative Example 1-1, it can be seen that when no alloy powder is added, the polar difference in size and magnetic properties of the NdFeB magnets all fluctuate to different degrees, among which the non-uniformity in the magnet dimensions is serious, the polar difference in magnet dimensions increases obviously, the effect of the polar difference on Br does not become apparent, and Hcj decreases by about 0.4 kOe.
[0090] Comparing Example 1 and Comparative Examples 1-2, it can be seen that when the Si content in the added alloy powder is 40% (i.e., above the specified range), it does not significantly affect the dimensional uniformity, but the Br of the magnet is significantly reduced by about 0.2 kGs, and the reduction in Hcj of the magnet is also somewhat larger, by about 0.80 kOe.
[0091] FIG. 1 is a schematic diagram of the grain boundary phase in the magnet of Example 1, in which the R-rich phase is enriched with alloy powder particles or in a molten state.
[0092] 2 is an EPMA detection diagram of the Si element in the magnet of Example 1. EPMA and spectrum analysis show that Si is enriched in the R-rich phase (the R-rich phase means a phase in which the mass content of element R is greater than 30%, where R means Nd and Pr), of which the mass content of Si is in the range of 1% to 5%.
[0093] FIG. 3 is an EPMA detection image of Si element in the magnet of Comparative Example 2.
[0094] Comparing the test results of Example 1 and Comparative Example 2, and combining EPMA and spectrum analysis, it can be seen that when the additives were added before melting, the Si was mainly distributed in the main phase and some of the main phase structure was destroyed, so the Br and Hcj of the magnets were both reduced to different degrees; on the other hand, when the additives were added before melting, the additives could not disperse the RFeBM powder in the pressing process, so the powder fluidity was still not ideal, resulting in serious dimensional non-uniformity of the magnets and an obvious increase in polarity difference.
[0095] The exemplary embodiments of the present invention have been described above. However, the scope of the claims of the present application is not limited to the above embodiments. Any modifications, equivalent replacements, improvements, etc. made by those skilled in the art without departing from the spirit and principles of the present invention should be included in the scope of the claims of the present invention. [Brief description of the drawings]
[0096] [Figure 1] FIG. 1 is a schematic diagram of a neodymium-iron-boron sintered magnet produced according to the present invention. [Diagram 2] FIG. 2 is an EPMA detection image of Si element in the sample of Example 1. [Diagram 3] FIG. 13 is an EPMA detection image of Si element in the sample of Comparative Example 2.
Claims
1. Neodymium iron boron sintered magnets are made of the following elements: R: its mass content is 26% to 30%, Fe: its mass content is 60% or more; B: The mass content is 0% to 1.5% and does not include 0%; M: its mass content is 0% to 3% and does not include 0%; Si: its mass content is 0.05% to 0.2%; the neodymium-iron-boron based sintered magnet includes a main phase and a grain boundary phase, the grain boundary phase further includes an R-rich phase, and the mass content of R in the R-rich phase is ≧30%, In the neodymium-iron-boron based sintered magnet, Si is enriched in the R-rich phase, and the mass content of Si is 1% to 5%; The size of the neodymium-iron-boron sintered magnet is a length of 10 mm to 20 mm, a press height of 8 mm to 15 mm, and an orientation length of 10 mm to 29 mm; R includes at least Pr and / or Nd, and optionally includes or excludes one or more of Dy, Tb, Ho, Gd, Ce, La, Y; M is one or more selected from Ti, Zr, V, Nb, Cu, Zr, Al and Ga elements; The neodymium-iron-boron based sintered magnet does not contain Co.
2. The neodymium-iron-boron sintered magnet has good dimensional uniformity, B: its mass content is 0.5% to 1.5%; The neodymium-iron-boron sintered magnet according to claim 1, characterized in that M has a mass content of 0.5% to 3%.
3. The weight of the neodymium-iron-boron sintered magnet is less than 50 g; The neodymium-iron-boron based sintered magnet has at least one of the following magnetic properties: Br is selected from 13.8 kGs to 14.8 kGs; 2. The neodymium-iron-boron sintered magnet according to claim 1, wherein Hcj is selected from the range of 14 kOe to 16 kOe.
4. A method for producing a neodymium-iron-boron sintered magnet according to claim 1, comprising the steps of: (1) producing RFeBM scales; (2) preparing an additive; (3) milling the RFeBM scales and mixing them with the additive to obtain a mixed powder; (4) A method for producing a neodymium-iron-boron based sintered magnet, comprising the steps of: preparing the mixed powder into a compact; and performing a sintering process to obtain the neodymium-iron-boron based sintered magnet.
5. In step (1), the RFeBM flakes are composed of the following elements, by weight: R: its mass content is 26% to 30%, Fe: its mass content is 60% or more; B: The mass content is 0% to 1.5% and does not include 0%; M: its mass content is 0% to 3% and does not include 0%; R includes at least Pr or Nd, and optionally includes or excludes one or more of Dy, Tb, Ho, Gd, Ce, La, Y; 5. The method according to claim 4, wherein M is one or more selected from the group consisting of Ti, Zr, V, Nb, Cu, Zr, Al and Ga elements, and M does not include Co.
6. In step (2), the additive comprises an M'Si alloy powder and / or an M'SiFe alloy powder, where M' is one or more selected from the group consisting of Al, Mg, Cu, Ni, Nb, Zr, and Ti metal elements; The method according to claim 4, wherein the powder particle size of the additive is 8 to 30 μm.
7. The M'Si alloy powder contains 30 wt% to 70 wt% M' and 15 wt% to 35 wt% Si, The M'SiFe alloy powder contains 20 wt % to 30 wt % M', 10 wt % to 15 wt % Si, and the balance is Fe; 7. The method according to claim 6, wherein the additive comprises M'Si alloy powder and M'SiFe powder, and the mass ratio thereof is (1-4):
1.
8. In step (3), the particle size of the RFeBM powder is smaller than the powder particle size of the additive; In step (3), the milling includes hydrogen pulverization milling and jet milling; In step (3), the mixing refers to adding the additive during the milling process or after milling is completed; The manufacturing method according to claim 4, characterized in that in step (3), the mass ratio of the RFeBM powder to the additive is 1000:(0-5), and does not include 0.
9. In step (4), the density of the powder compact is 4 to 5 g / cm 3 , In step (4), the size of the green compact is 12 mm to 24 mm in length, 9.2 mm to 17.2 mm in press height, and 14 mm to 38.5 mm in orientation length; In step (4), the method for producing the powder compact includes press molding under a magnetic field condition, 5. The method according to claim 4, further comprising the step of performing an isostatic pressing process after the press molding.
10. In step (4), the sintering process includes stepwise heating, vibration pressure sintering, and cooling; The stepwise heating conditions are that the heat treatment temperature is 100 to 1200° C., and the heat treatment temperature retention time is 0.5 to 20 hours. The stepwise temperature increase includes a multi-stage heating process. The stepwise heating may be carried out under an inert gas condition or under a vacuum condition; The stepwise heating includes heating to 100-450°C in the first step and maintaining the temperature for 0.5-2 hours, heating to 400-650°C in the second step and maintaining the temperature for 0.5-2 hours, heating to 600-900°C in the third step and maintaining the temperature for 0.5-2 hours, and heating to 1000-1100°C in the fourth step and maintaining the temperature for 1-3 hours; The vibration pressure sintering includes at least one gas-injection temperature lowering and at least one vacuum-injection temperature raising, and the gas-injection temperature lowering and the vacuum-injection temperature raising are alternately performed; The gas-filled temperature reduction refers to filling with an inert gas and lowering the temperature to 900 to 1050°C. The vacuum evacuation heating refers to evacuation and heating to 1000 to 1100°C. The cooling temperature refers to cooling to 100° C. or less after the vibration pressure sintering. The method according to claim 4, wherein the heating rate during the stepwise heating, the vibration pressure sintering and the cooling and decreasing are 5 to 10°C / min and 3 to 8°C / min, respectively.
Citation Information
Patent Citations
Alloy for r-t-b-based rare earth sintered magnet, method for manufacturing the same, alloy material for the same, r-t-b-based rare earth sintered magnet, method for manufacturing the same, and motor
JP2013216965A
R-t-b based permanent magnet
JP2020136531A
R-t-b sintered magnet and production method therefor
WO2018101402A1